Construction Management and Design of Industrial Concrete and Steel Structures. - El-Reedy, Mohamed A. (CRC Press, 2010)
A worldwide boom in the use of reinforced concrete structures for industrial projects has resulted in a wealth of new research leading to improved quality and lowered costs. Drawing on the best practices currently employed, this resource provides design and structural engineers with complete coverage of all the latest in the design, materials, construction, and maintenance of reinforced concrete and steel structures. In addition to vast technical engineering information, it provides detailed coverage of construction management issues, including quality control, project and risk management, tec.